Issues and challenges in evaluating community impact study on knowledge transfer program: researchers' reflection - Madon, Zainal; Surif, Misni; Abu Samah, Asnarulkhadi; Muhammad, Mahazan; Sulaiman, Abdul Hadi (Human Resource Management Academic Research Society, 2021)
Knowledge Transfer Program (KTP) is Malaysian government’s initiative to transfer the required skills and knowledge from higher education institutions to the community. Evaluation of the KTP is part of the agenda to examine the impacts of the KTP on society. This study is among the pioneer researches to analyze the issues in conducting the community impact study. The study adopted qualitative research design using researcher’s reflexivity approach. A total of 16 KTP communities’ projects for the first rolling (2011 – 2013) were examined. The findings indicate that there are five core issues that emerged through the reflexive process of conducting the study. They include absence of database, timeframe, multiple beneficiaries and poor assessment of community needs. These issues equally are important for stakeholders, researchers and practitioners. Few recommendations are also put forward to improve the community project evaluation in the future.